PENERAPAN SISTEM MANAJEMEN PENGETAHUAN PADA PERUSAHAAN KAISHOP COOKIES DENGAN METODE KMSLC - Atmojo, Ruben Dwijaya Setyo; Gunawan, Stefanus Christian (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2025)
This document discusses the implementation of a Knowledge Management System (KMS) in the company Kaishop Cookies, which focuses on selling mochi products. The main objective of the research is to identify and map the knowledge that exists within the company, both explicit and tacit, in order to improve the quality of services and products. The methodology used is a knowledge mapping approach with the Knowledge Management System Life Cycle (KMSLC) framework, which includes needs analysis, system design, development, implementation, evaluation, and maintenance. The results of the study show that explicit knowledge such as menu lists and product prices are often not well documented, while tacit knowledge related to the determination of shipping and product prices does not run optimally. By managing knowledge on a regular basis, Kaishop Cookies can improve business processes and competitiveness in the market. This research also provides recommendations to improve product quality based on criticism and suggestions from consumers. The conclusion of this study emphasizes the importance of knowledge management in the culinary business. Effective implementation of KMS can help companies in planning better strategies and increasing customer satisfaction. Thus, the implementation of a knowledge management system is the key to success for Kaishop Cookies in facing challenges in a competitive industry.